Bahasa Arab: “Ruh” Pendidikan Islam - Adhriansyah A. Lasawali (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
This research examines the urgency (benefits) of Arabic for Islamic education. After the researchers studied and analyzed, Arabic is a very important language to learn in understanding Islamic education. This is not only because the Arabic language is the language of the holy book of Islam (the Qur'an) and the Hadith of the Prophet Muhammad, but more than that, this language is used in books and as the source of Islamic teachings, such as fiqh, hadith, ulumul qur'an, tafsir, tauhid and so on. In other words, Arabic is the language of "savior" of Islamic education, without Arabic Islamic education will experience extinction (destruction). In the early days of the spread of Islam, Arabic was the language used in politics and government administration as well as the language of religion. Even after Islam expanded its power, this language was still used as the main language, until Islamic power fell into the hands of the Saljuk Bani kingdom in the east and the Ottoman Turks in Turkey this language was no longer the language of government administration or the language of the state, but only became the language of religion, because The Saljuqs spoke Persian and the Ottoman Turks used Turkish as the official language of their government.